2017
DOI: 10.3390/toxins9110354
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Reveals Specific Interaction Sites between Scorpion Toxins and Kv1.2 Channel: Implications for Design of Highly Selective Drugs

Abstract: The Kv1.2 channel plays an important role in the maintenance of resting membrane potential and the regulation of the cellular excitability of neurons, whose silencing or mutations can elicit neuropathic pain or neurological diseases (e.g., epilepsy and ataxia). Scorpion venom contains a variety of peptide toxins targeting the pore region of this channel. Despite a large amount of structural and functional data currently available, their detailed interaction modes are poorly understood. In this work, we choose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The system is solvated by the truncated octahedron TIP3PBOX at 12 Å distance from the edge of the octahedron. Note that the amino acid residues TRP-26 and TRP-113, at the intracellular ends of transmembrane α helices M1 and M2, respectively, and TRP-87 at the extracellular end of M2, which are involved in the interaction with the lipid bilayer, are not involved in the internal blocking action of QA. , Previous reports indicated that binding of blocker molecules hardly affects the overall stability of the K + channels and the interaction is hardly affected by the membrane. Also, many simulation studies on the binding of blocker molecules and K + channels without a membrane have achieved good agreement with the experimental data. , Moreover, discarding the lipid–protein interactions has also contributed to the reduction of the computational time. Thus, we did not add the membrane into the simulation, but rather perform the simulation by maintaining a restraint weight of 0.5 kcal/mol/Å 2 on the C α atom of protein during the production runs to mimic the stabilizing effect of the lipid bilayer on the tetrameric ion channel, while the side chains and QAs are allowed to move freely.…”
Section: Computational Detailsmentioning
confidence: 86%
See 1 more Smart Citation
“…The system is solvated by the truncated octahedron TIP3PBOX at 12 Å distance from the edge of the octahedron. Note that the amino acid residues TRP-26 and TRP-113, at the intracellular ends of transmembrane α helices M1 and M2, respectively, and TRP-87 at the extracellular end of M2, which are involved in the interaction with the lipid bilayer, are not involved in the internal blocking action of QA. , Previous reports indicated that binding of blocker molecules hardly affects the overall stability of the K + channels and the interaction is hardly affected by the membrane. Also, many simulation studies on the binding of blocker molecules and K + channels without a membrane have achieved good agreement with the experimental data. , Moreover, discarding the lipid–protein interactions has also contributed to the reduction of the computational time. Thus, we did not add the membrane into the simulation, but rather perform the simulation by maintaining a restraint weight of 0.5 kcal/mol/Å 2 on the C α atom of protein during the production runs to mimic the stabilizing effect of the lipid bilayer on the tetrameric ion channel, while the side chains and QAs are allowed to move freely.…”
Section: Computational Detailsmentioning
confidence: 86%
“…Note that the amino acid residues TRP-26 and TRP-113, at the intracellular ends of transmembrane α helices M1 and M2, respectively, and TRP-87 at the extracellular end of M2, which are involved in the interaction with the lipid bilayer, are not involved in the internal blocking action of QA. 58,59 Previous reports indicated that binding of blocker molecules hardly affects the overall stability of the K + channels and the interaction is hardly affected by the membrane. 60−63 Also, many simulation studies on the binding of blocker molecules and K + channels without a membrane have achieved good agreement with the experimental data.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…In this work, we carried out mutational analysis of site 52 in three α-ScNaTxs. In combination with molecular dynamics simulations (Yuan et al 2017) and statistical coupling analysis (SCA) (Halabi et al 2009), our experimental data demonstrated that the accelerated substitutions of site 52 is a result of adaptation to the evolutionary change of the bioactive PSSs, and that such coevolution may help the substituted bioactive sites to maintain an active conformation for receptor binding. Our study thus suggests that within one nonenzymatic protein, there exists also allosteric communication between its bioactive and nonbioactive distant sites.…”
Section: Introductionmentioning
confidence: 81%
“…These toxins typically consist of 23-43 amino acid residues and are classified into four subfamilies, of which α-KTx is the largest subfamily that shares a common cysteine-stabilized α/β motif 53 . Given the high specificity and affinity of scorpion toxins for K + and other ion channels, their potential as lead candidates for drug discovery for ion channelopathies has been widely recognized 5,52,54 .…”
Section: Drug Discovery In Academia: Discovery Of Novel Lead Molecules From Scorpion Venomsmentioning
confidence: 99%